A conceptual paper on leisure time and travel habits among youth - Aikal Liyani Mohd Rasdi; Nurul Aziah Ahmad; Nurul Hafizah Mohd Yasin; Siti Aisah Abas; Zaharah Mohamed Rani; Khairun Najiah Ahmad (Faculty of Entrepreneurship and Business,UMK, 2015)
Youth travel market represents an important and booming component of the tourism market. Its evolution is largely connected to the general dynamic of tourism and at the same time, also records its own trends generated by the action of specific factors. The motivations that influence youth to go travel are to experience traveling, to see places, for historical and cultural value, to relax and to gain friends. The study objectives are to identify factors that influence youth to go travel during leisure time, to examine total average spending during travel and to identify activities carried on during travel. The major factors affecting travel choices among youth when identified, will have important implications in product development. Other than that, by knowing factors that influence youth to travel as well as their travel habits, tourism industry can fulfill they needs and wants.